Students’ Teaching Interest and Their Microteaching Learning Outcomes in Automotive Vocational Education - Bintha Ustafiano; Mentari Arisyid Mulyadi; Yolana Nursyafti; Fajar Maulana (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to determine the relationship between the interest in becoming a teacher and the microteaching learning outcomes of students in the Vocational Education Program in Automotive Technology at Universitas Lancang Kuning. This research uses a quantitative approach with a correlational method. The sample consisted of 42 students who had completed the microteaching course, and data were collected through an interest questionnaire and academic performance scores. Data analysis was conducted using the Pearson Product Moment correlation test with the help of SPSS. The results showed a strong and significant relationship between the interest in becoming a teacher and microteaching learning outcomes, with a correlation coefficient of 0.874 and a coefficient of determination of 76.4%. These findings indicate that a high interest in the teaching profession can positively contribute to students’ academic achievement. Therefore, fostering interest in the teaching profession should be a focus in learning strategies and career development for vocational education students.